Molecular regulation of autophagy in a pro-inflammatory tumour microenvironment: New insight into the role of serum amyloid A. (June 2021) - du Plessis, M.; Davis, T.; Loos, B.; Pretorius, E.; de Villiers, W.J.S.; Engelbrecht, A.M.
Highlights: Serum amyloid A (SAA) can modulate autophagy through multiple entry points in cancer cells. SAA can modulate autophagy positively or negatively, depending on cell type and cellular context. SAA receptor-binding can modulate autophagy in cancer by activating the PI3K/Akt/mTOR and the MAPK signaling pathways. SAA can regulate autophagy through its role as a pro-inflammatory cytokine. Regulation of autophagy by SAA can influence treatment outcomes, highlighting SAA as a potenital target for cancer treatment. Abstract: Chronic inflammation, systemic or local, plays a vital role in tumour progression and metastasis. Dysregulation of key physiological processes such as autophagy elicit unfavourable immune responses to induce chronic inflammation. Cytokines, growth factors and acute phase proteins present in the tumour microenvironment regulate inflammatory responses and alter crosstalk between various signalling pathways involved in the progression of cancer. Serum amyloid A (SAA) is a key acute phase protein secreted by the liver during the acute phase response (APR) following infection or injury. However, cancer and cancer-associated cells produce SAA, which when present in high levels in the tumour microenvironment contributes to cancer initiation, progression and metastasis. SAA can activate several signalling pathways such as the PI3K and MAPK pathways, which are also known modulators of the intracellular degradation process, autophagy. Autophagy can be regarded as having a double edged sword effect in cancer. Its dysregulation can induce malignant transformation through metabolic stress which manifests as oxidative stress, endoplasmic reticulum (ER) stress and DNA damage. On the other hand, autophagy can promote cancer survival during metabolic stress, hypoxia and senescence. Autophagy has been utilised to promote the efficiency of chemotherapeutic agents and can either be inhibited or induced to improve treatment outcomes. This review aims to address the known mechanisms that regulate autophagy as well as illustrating the role of SAA in modulating these pathways and its clinical implications for cancer therapy.